Single Agent Antihypertensive Therapy and Orthostatic Blood Pressure Behaviour in Older Adults Using Beat-to-Beat Measurements: The Irish Longitudinal Study on Ageing - Canney, Mark (PLoS One, 2016)
BACKGROUND: Impaired blood pressure (BP) stabilisation after standing, defined using beat-to-beat measurements, has been shown to predict important health outcomes. We aimed to define the relationship between individual classes of antihypertensive agent and BP stabilisation among hypertensive older adults. METHODS: Cross-sectional analysis from The Irish Longitudinal Study on Ageing, a cohort study of Irish adults aged 50 years and over. Beat-to-beat BP was recorded in participants undergoing an active stand test. We defined grade 1 hypertension according to European Society of Cardiology criteria (systolic BP [SBP] 140-159mmHg ± diastolic BP [DBP] 90-99mmHg). Outcomes were: (i) initial orthostatic hypotension (IOH) (SBP drop ≥40mmHg ± DBP drop ≥20mmHg within 15 seconds [s] of standing accompanied by symptoms); (ii) sustained OH (SBP drop ≥20mmHg ± DBP drop ≥10mmHg from 60 to 110s inclusive); (iii) impaired BP stabilisation (SBP drop ≥20mmHg ± DBP drop ≥10mmHg at any 10s interval during the test). Outcomes were assessed using multivariable-adjusted logistic regression. RESULTS: A total of 536 hypertensive participants were receiving monotherapy with a renin-angiotensin-aldosterone-system inhibitor (n = 317, 59.1%), beta-blocker (n = 89, 16.6%), calcium channel blocker (n = 89, 16.6%) or diuretic (n = 41, 7.6%). A further 783 untreated participants met criteria for grade 1 hypertension. Beta-blockers were associated with increased odds of initial OH (OR 2.05, 95% CI 1.31–3.21) and sustained OH (OR 3.36, 95% CI 1.87–6.03) versus untreated grade 1 hypertension. Multivariable adjustment did not attenuate the results. Impaired BP stabilisation was evident at 20s (OR 2.59, 95% CI 1.58–4.25) and persisted at 110s (OR 2.90, 95% CI 1.64–5.11). No association was found between the other agents and any study outcome. CONCLUSION: Beta-blocker monotherapy was associated with a >2-fold increased odds of initial OH and a >3-fold increased odds of sustained OH and impaired BP stabilisation, compared to untreated grade 1 hypertension. These findings support existing literature questioning the role of beta-blockers as first line agents for essential hypertension.